基于UWB的车间物料配送控制与管理平台 (2018)
种基于UWB的车间物料配送控制与管理平台，它包括智能后台控制模块与自动化管理模块，其特征是：所述的智能后台控制模块包括核心路由（1）、通讯服务（2）、实时定位（3）；核心路由（1）提供封装的跨模块调用接口，完成数据源与目标组间的数据路由，简化数据交叉传送复杂性；通讯服务（2）封装通讯协议与数据交换功能，实现平台与小车双向通信，并将平台控制数据和小车运行状态监测数据发送至核心路由（1），通过其转发将数据发送至数据库服务模块（5）与客户端服务模块（6）。本发明为车间物流配送小车提供了理想的数据支持，能提高配送效率。 A workshop material delivery control and manage platform based on UWB is provided, comprising an intelligent background control module and an automated management module. The platform is characterized in that: the intelligent background control module comprises a core route (1), a communication service (2), and real-time positioning (3); the core route (1) provides a packaged cross-module calling interface, completes data routing between data source and target groups and simplifies data cross transferring complexity; the communication service (2) is used for packaging communication protocols and data exchanging functions, realizing bidirectional communication between the platform and trolleys, sending platform control data and trolley operation status mon